ATR kinase activity promotes antibody class switch recombination in B cells through cell cycle regulation without suppressing DSB resection and microhomology usage. Issue 6 (22nd April 2021) - Sun, Xikui; Liu, Meiling; Bai, Jingning; Xu, Jiejie; Zhu, Chengming; Dong, Junchao; Chen, Chun
Abstract: Class switch recombination (CSR) changes the effector functions of antibodies and is carried out by classical and alternative nonhomologous end joining (c-NHEJ and A-EJ) of repetitive switch (S) region double-strand breaks (DSBs). The master DNA damage response (DDR) kinase ataxia-telangiectasia mutated (ATM) is critical for CSR in part by suppressing S region DSB resection. However, whether another related DDR kinase ATM- and Rad3-related (ATR) plays similar role in CSR remains elusive. In this study, we investigated the requirement for ATR kinase activity on CSR in both c-NHEJ competent and deficient B cell lines with high-throughput sequencing of S-S junctions. We found that ATR kinase inhibition efficiently blocked both c-NHEJ- and A-EJ-mediated CSR without affecting germline transcription and activation-induced cytosine deaminase expression. In contrast to ATM, ATR does not suppress S region DSB resection and microhomology usage. In addition, ATR kinase inhibition did not affect Cas9-generated DSB end joining by either c-NHEJ and A-EJ. ATR kinase-inhibited stimulated B cells proliferate much slower than controls and exhibited altered cell cycle profile with increased G1 and G2/M phase cells. In summary, our data revealed a role for ATR in promoting both c-NHEJ- and A-EJ-mediated CSR through regulating cell proliferation upon damage without negatively influencing DSB end-joining features. Graphical Abstract: Unlike ATM, ATR kinase activity promotes both c-NHEJ and A-EJ-mediated CSR through cell cycle regulation but not suppression of DSB resection and MH usage